2020
DOI: 10.1093/jas/skaa022
|View full text |Cite
|
Sign up to set email alerts
|

Effects of vitamin B6 on the growth performance, intestinal morphology, and gene expression in weaned piglets that are fed a low-protein diet1

Abstract: Vitamin B6 (VB6), which is an essential functional substance for biosome, plays an irreplaceable role in animal health. However, there are few studies that focus on the correlation between VB6 and intestinal health in weaned piglets. This study was conducted to investigate the effects of VB6 on the growth performance, intestinal morphology, and inflammatory cytokines and amino acid (AA) transporters mRNA expression in weaned piglets that are fed a low crude-protein (CP, 18%) diet. Eighteen crossbred piglets wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 42 publications
0
23
0
Order By: Relevance
“…The rumen was separated from each sheep, and approximately 100 ml of rumen content was collected and transferred into two 50 ml sterile plastic tubes and then immediately stored at −80°C. A 1 × 1 cm section of the rumen wall was cut, approximately 2 cm long intestinal tissues (duodenum, jejunum, and ileum) from the middle sections were isolated and flushed with ice‐cold phosphate‐buffered saline, and then all the samples were immediately fixed in 4% neutral formalin for morphometric analysis (Yin et al., 2020).…”
Section: Methodsmentioning
confidence: 99%
“…The rumen was separated from each sheep, and approximately 100 ml of rumen content was collected and transferred into two 50 ml sterile plastic tubes and then immediately stored at −80°C. A 1 × 1 cm section of the rumen wall was cut, approximately 2 cm long intestinal tissues (duodenum, jejunum, and ileum) from the middle sections were isolated and flushed with ice‐cold phosphate‐buffered saline, and then all the samples were immediately fixed in 4% neutral formalin for morphometric analysis (Yin et al., 2020).…”
Section: Methodsmentioning
confidence: 99%
“…The level of protein is an important factor affecting the growth performance and intestinal health of piglets [ 14 , 15 ]. The undigested protein of piglets will enter the large intestine for fermentation in order to produce toxic metabolites, which will destroy the integrity of the intestinal epithelium and damage the health of the intestinal tract [ 16 ]. Many studies have shown that reducing protein levels can reduce the diarrhea rate and N excretion of piglets, and can reduce protein fermentation in the intestinal tract [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…All experiments in the present study were conducted according to the guidelines of animal welfare in China, and the experimental design and procedures were reviewed and approved (Approval number 2016-093) by the Animal Care and Use Committee of Hunan Normal University, Changsha, Hunan province, China ( Yin et al., 2020 ).…”
Section: Methodsmentioning
confidence: 99%